ANALISIS TUGAS CAMAT DALAM KEWENANGAN PELAYANAN ADMINISTRASI TERPADU KECAMATAN (STUDI KASUS DI KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU TAHUN 2013) - Dicki Sahendra; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Integrated Administrative Services District of the authority of the public service in the district of which the management of the request to the stage of publication of documents done in one place. One place here means simply through a table or counter service. The problem is how to optimize the role of the Integrated Administrative Services Sub-district to improve the quality of public services in accordance with the expectations of society as a customer in order to realize the Good Local Government, to review the case in Indragiri Hulu. As a service center, in the sense that the future sub-districts are expected to provide services to the community proportionally based on the criteria and sub-district scale in the field of licensing and non-licensing. The purpose of this study was to determine the assignment of authority district head in Subdistrict Administrative Services Integrated especially in Sub Sand Turtle Indragiri Hulu Year 2013. In this study, the concept used refers to the Minister of Home Affairs No. 4 of 2010 on Guidelines for Integrated Administrative Services Sub-district. This study used a descriptive study using a qualitative method approach. In the data collection techniques researchers used questionnaires, interviews and documentation. The results of this study can be concluded that the task of the authority of the district head Subdistrict Administrative Services Integrated especially in Sub Sand Turtle Indragiri Hulu Year 2013 has been carried out quite well. For facilities that are expected to carry out the operations, both in quality and quantity, especially computer and printer facilities to support services in the District Patents Sand Turtle. To supervise and control of the executive apparatus, so as to implement, utilize effectively working hours. By way of enforcing labor discipline while providing sanctions in accordance with applicable regulations.Keywords: Authority, Care, Integrated Administration